2013
DOI: 10.1186/1471-227x-13-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk and clinical-outcome indicators of delirium in an emergency department intermediate care unit (EDIMCU): an observational prospective study

Abstract: BackgroundIdentification of delirium in emergency departments (ED) is often underestimated; within EDs, studies on delirium assessment and relation with patient outcome in Intermediate Care Units (IMCU) appear missing in European hospital settings. Here we aimed to determine delirium prevalence in an EDIMCU (Hospital de Braga, Braga, Portugal) and assessed routine biochemical parameters that might be delirium indicators.MethodsThe study was prospective and observational. Sedation level was assessed via the Ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 28 publications
(43 reference statements)
3
15
0
6
Order By: Relevance
“…The incidence of delirium has been reported to range 20-30% in patients hospitalized in general wards (Juliebo et al, 2009;Mariz et al, 2013;McPherson et al, 2013;Sharma et al, 2012;Van Rompaey et al, 2009), 36-44% in elderly post-surgery patients (Juliebo et al, 2009;Robinson et al, 2009), and 32-87% in patients hospitalized in the intensive care unit (ICU) (Ouimet et al, 2007;Vasilevskis et al, 2012;Wells, 2012). Although the incidence of delirium in Korea has been reported as 22% in ICU patients and 10-32% in post-surgery elderly patients (Kang et al, 2011;Kim et al, 2008), an incidence of 26% in ICU patients was reported in a recent large-scale study reported (Moon et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of delirium has been reported to range 20-30% in patients hospitalized in general wards (Juliebo et al, 2009;Mariz et al, 2013;McPherson et al, 2013;Sharma et al, 2012;Van Rompaey et al, 2009), 36-44% in elderly post-surgery patients (Juliebo et al, 2009;Robinson et al, 2009), and 32-87% in patients hospitalized in the intensive care unit (ICU) (Ouimet et al, 2007;Vasilevskis et al, 2012;Wells, 2012). Although the incidence of delirium in Korea has been reported as 22% in ICU patients and 10-32% in post-surgery elderly patients (Kang et al, 2011;Kim et al, 2008), an incidence of 26% in ICU patients was reported in a recent large-scale study reported (Moon et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first hospital-based study to evaluate the relationship between delirium and length of hospital stay among medical inpatients in Nigeria. [13] and China [14], which all indicated that delirium was an independent risk factor for pronged length of hospital stay. However, there are sparse data on differential effects of delirium on clinical outcomes including length of hospital stay in Nigeria.…”
Section: Discussionmentioning
confidence: 91%
“…Um estudo avaliou a prevalência de delirium numa unidade de cuidados intermédios de um serviço de urgência identificando o mesmo em 20,1% da população. 17 Uma tese de mestrado identificou numa população de doentes seguidos na consulta de suporte intra-hospitalar e consulta externa de um serviço de cuidados paliativos, uma prevalência de 41,2% de delirium 18 Numa unidade de Acidente Vascular Cerebral (AVC) constatou-se num período de cinco anos o diagnóstico de delirium em 10,2% dos doentes admitidos. 19 Num outro estudo realizado numa enfermaria de medicina interna no período de um ano, constatou-se nos últimos 20 dias de internamento a prevalência de 2,5% de delirium nos doentes que morreram.…”
Section: Epidemiologiaunclassified